the Balinese Pop Song which was Semiotic Heuristic study - Ni Wayan Sariani; Rasna, I Wayan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2020)
Abstract. This research was about Balinese pop song which was Semiotic Heuristic study. The research underlined was the fact that occurred in the Balinese popular songs as a part of the literary work featured new vocabularies as well as old vocabularies modification and also a combination of vocabularies from other languages such as Indonesian and English, considered as the